2013
DOI: 10.1088/1367-2630/15/10/103008
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of cross-plane polaronic transport and resistive switching in Pt–Pr0.67Ca0.33MnO3–Pt heterostructures

Abstract: The identification of the cross-plane electric transport mechanisms in different resistance states of metal-oxide sandwich structures is essential for gaining insights into the mechanisms of resistive switching (RS). Here, we present a systematic study of cross-plane electric transport properties of Pr 0.67 Ca 0.33 MnO 3 (PCMO) thin films sandwiched by precious Pt metal electrodes. We observe three different transport regimes: ohmic, nonlinear and RS. The nonlinear regime is associated with colossal magneto-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 26 publications
0
24
1
Order By: Relevance
“…(9) and only two local phonon states are needed to construct the ground state of Eq. (14): the first one is the phonon vacuum state if the site is not occupied by the electron, and the second one is a coherent state of phonons if the site is occupied by the electron. Thus two phonon states (for each site) build an optimal basis for the ground state.…”
Section: A Optimal Phonon Modesmentioning
confidence: 99%
“…(9) and only two local phonon states are needed to construct the ground state of Eq. (14): the first one is the phonon vacuum state if the site is not occupied by the electron, and the second one is a coherent state of phonons if the site is occupied by the electron. Thus two phonon states (for each site) build an optimal basis for the ground state.…”
Section: A Optimal Phonon Modesmentioning
confidence: 99%
“…4, we show the systematic dependence of RðtÞ as a function of the applied external (electronic) current. Along with the simulations of the VEOVM, we also present our experimental results measured on a manganite-based (La 0.325 Pr 0.300 Ca 0.375 MnO 3 ) memristive device [34][35][36][37][38]. The experimental setup and device are described in detail in Appendix F and in Ref.…”
mentioning
confidence: 99%
“…[13][14][15][16] Also, metal electrodes have been used to control resistive switching in mixed valent manganites. 17,18 Multilayered structures consisting of more than one manganite have been reported for various potential applications. [19][20][21] Jo et al 19 have demonstrated the tunneling magnetoresistance (TMR) effect across the La 0.7 Ca 0.3 MnO 3 /La 0.45 Ca 0.55 MnO 3 / La 0.7 Ca 0.3 MnO 3 manganite based trilayered magnetic tunnel junctions.…”
mentioning
confidence: 99%